Marjambar as a Symbolic Interaction of the Bunga Bondar Society in Sipirok District - North Sumatra - Indra Muda; Syafruddin Ritonga; Beby Masitho Batubara; Nina Angelia; Waridah Pulungan (Ikatan Sarjana Komunikasi Indonesia, 2022)
Bunga Bondar Village has a unique culture called Marjambar. Marjambar is held by distributing pastries typical of the local community during religious holidays, which are ahead of Eid al-Fitr for Muslims and one day before New Year for Christians. This study aims to analyze the multiculturalism model that exists in marjambar. This study uses Mead's symbolic interaction theory. The research method of this study is a qualitative descriptive approach, while data collection technique is conducted through observation, interviews and documentation. A total of eight research informants were interviewed, comprising two Islamic religious leaders, two Christian religious leaders, one traditional leader, one youth leader, two village apparatuses. This research found that in realizing the values of multiculturalism there is a philosophy of life